Antepartum Depression among Pregnant Women Attending Antenatal Care (ANC) Services in Tertiary Hospital of Nepal - Paudel, Bimal; Sapkota, Narayan; Shrestha, Sumnima; Giri, Mahendra; Pandit, Shailesh (NPRC Journal of Multidisciplinary Research, 2025)
Background: Antepartum depression is common complication of women during pregnancy, May affects the mother, child and family adversely with serious consequences like maternal suicide if it left untreated. To assess antepartum depression among pregnant women, a hospital-based cross-sectional study was conducted in Bharatpur Hospital of Chitwan. Methodology: A cross sectional study was conducted in a tertiary level government hospital using convenient sampling method. A total of 252 pregnant women were interviewed with semi structured questionnaire including Edinburg Postpartum Depression scale (Sensitivity-68.4, Specificity -93.8) to screen for antepartum depression. Data was entered on Epi-data and further analyzed using SPSS. Results: Out of 252 respondents, 16.7 % were with antepartum depression while 83.3% recorded no antepartum depression. Loneliness (AOR= 24.96, 95% CI (2.92-213.45) and self-harm (AOR= 3.39, 95%CI (1.11-10.38) had higher odds of having antepartum depression. Conclusions and Recommendations: The study indicates that feeling of self-harm thoughts and thought of loneliness are much important for reducing the problem burden of antepartum depression which affects the health of both mother and child. So, further efforts should be considered and programs targeting health related quality of pregnant women should be incorporated in developing countries like Nepal.